Prevención y control de la contaminación en la industria manufacturera sub-sector curtiembre, implementando un programa de producción más limpia en la empresa Quimipiel S.A.C. - Ríos Pozo, Juan Eduardo (2006)
The entry of Peru into a globalized economy implies higher quality, greater competitiveness, better use of our skills for innovation and technological development, this forces companies to make appropriate use of environmental management tools adapting them to the circumstances that arise. , to achieve leadership and business success. Aware of this, we present at your discretion, the following study entitled "Prevention and control of pollution in the manufacturing industry sub-sector tannery, implementing a program of Cleaner Production in the company Quimipiel SAC", with the priority of establishing bases solid that guarantee an efficient environmental management oriented towards its modernization and integral development. For this purpose, this program contains several chapters in which is the reference framework for the development of this study, the description of the subsector tanneries and their relationship with our environment, the description of the processes in tanneries and their discharges the environment , the methodology of the PML, finally the recommendations and economic evaluation